Outcomes and survival following neoadjuvant chemotherapy versus neoadjuvant chemoradiotherapy for cancer of the esophagus: Inverse propensity score weighted analysis. Issue 12 (December 2020) - Pucher, Philip H.; Rahman, Saqib A.; Walker, Robert C.; Grace, Ben L.; Bateman, Andrew; Iveson, Tim; Jackson, Andrew; Rees, Charlotte; Byrne, James P.; Kelly, Jamie J.; Noble, Fergus; Underwood, Timothy J.
Abstract: Background: Esophageal cancer is increasingly common and carries a poor prognosis. The optimal treatment modality for locally advanced cancer is unknown, with current guidance recommending either neoadjuvant chemotherapy (CT) or chemoradiotherapy (CRT) followed by surgery. There is a lack of adequately powered trials comparing CT against CRT. We retrospectively compared CT versus CRT using a propensity score weighting approach. Methods: Demographic, disease, treatment and outcome data were retrieved from a local database for patients who received neoadjuvant CT or CRT followed by surgery. Inverse probability of treatment weighting (IPTW) was used to balance groups using a propensity score-weighting approach. Groups were assessed for differences in postoperative outcomes and survival. Kaplan-Meier and non-parametric tests were used to compare survival and outcome data as appropriate. Results: Data for 284 patients were retrieved. Following IPTW groups were well matched. No significant differences were seen for postoperative complications (CT 64.9% vs. CRT 63.3%, p = 0.807), including major complications (24.0% vs. 23.6%, p = 0.943) and anastomotic leak (7.8% vs. 5.6%, p = 0.526). Significantly higher rates of clinical regression and complete pathological response were seen following CRT (p = 0.002 for both). Rates of R0 resection were higher with CRT, CT 79.1% vs. CRT 93.1%, p = 0.006. There was no difference between groups for overall or disease-free survival. Conclusion: This study suggests that the significant improvements in local tumour response seen after neoadjuvant CRT compared to CT may not translate to different survival outcomes. However, it must be stressed that adequately powered prospective trials are still lacking.